ANALISIS BIOINFORMATIKA BERBASIS WEB PADA SEKUEN GENOM PARSIAL SAGU (Metroxylon sagu Rottb.) - Purwoko, Devit; Cartealy, Imam Civi; Tajuddin, Teuku; Dinarti, Diny; Sudarsono, Sudarsono (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2018)
WEB-based bioinformatic analysis on partial genome sequence of Sago (Metroxylon sagu Rottb.)ABSTRACTSago genome sequencing analysis is still very limited. This study is a preliminary study of sago sequence analysis obtained from NGS technology to understand and identify new genetic sequences that have homology to genes in the NCBI database. Sequences were analyzed using Blast2Go to determine the genetic function annotation, putative gene identification was performed on the Arabidopsis database using the BLASTx program with a 10-3 e-value limit on The Arabidopsis Information Resource (TAIR) (http://www.arabidopsis.org/index.jsp). Gene interactions were analyzed using DAVID and GeneMania programs. Based on sequence analysis with Blast2Go, 33 sequences with Blastx hit consisting of: 29 sequences had a high homology. The sago sequences with a similarity of ≥ 90% are glutamate decarboxylase and HT1-like serine threonine kinase with hit number 10. The distribution of interactions between genes from GeneMania analysis is known to be mostly interconnected in the 65.13% protein domain, predicted 19.83%, genes with 14.47% shared expression and the remaining 0.57% had localization together.Keywords: bioinformatics, gene annotation, gene ontology, genome sequence, Metroxylon sagu ABSTRAKKajian analisis sekuen genom sagu hingga saat ini masih amat terbatas. Penelitian ini merupakan riset pendahuluan analisis sekuen sagu yang diperoleh dari teknologi NGS untuk mengetahui dan mengidentifikasi sekuen gen baru yang memiliki homologi dengan gen pada database NCBI. Sekuen dianalisis menggunakan perangkat Blast2Go untuk mengetahui anotasi fungsional gen, identifikasi gen putatif dilakukan terhadap database Arabidopsis menggunakan program BLASTx dengan batas e-value 10-3 pada The Arabidopsis Information Resource (TAIR). Interaksi gen dianalisis menggunakan program DAVID dan GeneMania. Berdasarkan analisis sekuen dengan Blast2Go, diperoleh 33 sekuen dengan Blastx hit yang terdiri atas: 29 sekuen memiliki homologi yang tinggi. Gen dengan rataan kemiripan ≥ 90% adalah glutamate decarboxylase dan serine threonine-kinase HT1-like dengan jumlah hit 10. Persebaran interaksi antar gen hasil analisis GeneMania diketahui sebagian besar saling terkait pada domain protein 65,13%, koneksi yang berhasil diprediksi 19,83%, gen dengan ekspresi bersama 14,47% dan sisanya 0,57% memiliki peranan bersama. Kata Kunci: anotasi gen, bioinformatika, Metroxylon sagu, ontologi gen, sekuen genome